The Effectiveness of Plaza Dancing on Psychological Well-Being and Ill-Being: A Systematic Review and Meta-Analysis - Bai, Zhenggang; Li, Yixuan; Yang, Yufan; Xie, Chengdan; Zhu, Zhengyun; Xu, Yan; Bai, Ruhai (Frontiers in Psychology, 2022)
Evidence suggests that participation in plaza dancing may affect mental health. This study for the first time quantified the relationships between plaza dancing and psychological well-being and ill-being. We systematically searched PubMed, Web of Science, CNKI, Wanfang and VIP to identify relevant studies published from database inception to 25 July 2021. The standardized mean differences (SMDs) of pre-to-post intervention data were calculated in the meta-analysis. Subgroup and meta-regression analyses were performed to test the potential moderating effects of age, outcome classification, measurement instruments, district, publication year, total sample size, and the duration, frequency and length of the square dance intervention. A total of 25 original articles met all the eligibility criteria and were included in the review, and seventeen studies were included in the meta-analysis. The meta-analysis revealed that plaza dancing improved psychological well-being (pooled SMD=0.76; 95% CI: 0.58, 0.95; I2 = 86.9%) and reduced psychological ill-being (pooled SMD=-0.84; 95% CI: -1.00, -0.68; I2 = 64.8%). The study participants’ age and district did not seem to affect the effectiveness of the plaza dancing intervention. The duration and frequency of plaza dancing affected the association between square dance and psychological well-being (duration, =-0.044; 95% CI: -0.085, -0.004; frequency, =0.122; 95% CI: 0.024, 0.221) and psychological ill-being (duration, =-0.029; 95% CI: -0.040, -0.018; frequency, =0.154; 95% CI: 0.030, 0.278). Plaza dancing has a significant positive effect on psychological well-being and psychological ill-being, and the effects are moderated by intervention modality. Generalizing plaza dancing interventions to promote psychological well-being and prevent or treat psychological ill-being is needed.